Nature's magic synergy in evolution and the fate of humankind - Corning, Peter A. 1935- (Cambridge University Press, 2003)
Nature's Magic, first published in 2003, presents a bold vision of the evolutionary process from the Big Bang to the 21st century. Synergy of various kinds is not only a ubiquitous aspect of the natural world but it has also been a wellspring of creativity and the 'driver' of the broad evolutionary trend toward increased complexity, in nature and human societies alike. But in contrast with the many theories of emergence or complexity that rely on some underlying force or 'law', the 'Synergism Hypothesis', as Peter Corning calls it, is in essence an economic theory of biological complexity; it is fully consistent with mainstream evolutionary biology. Corning refers to it as Holistic Darwinism. Among the many important insights that are provided by this new paradigm, Corning presents a scenario in which the human species invented itself; synergistic, behavioral and technological innovations were the 'pacemakers' of our biological evolution. Synergy has also been the key to the evolution of complex modern societies, he concludes.